2004
DOI: 10.2337/diacare.27.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Type 2 Diabetes and Impaired Glucose Metabolism

Abstract: OBJECTIVE -To assess the Australian protocol for identifying undiagnosed type 2 diabetes and impaired glucose metabolism. RESEARCH DESIGN AND METHODS -TheAustralian screening protocol recommends a stepped approach to detecting undiagnosed type 2 diabetes based on assessment of risk status, measurement of fasting plasma glucose (FPG) in individuals at risk, and further testing according to FPG. The performance of and variations to this protocol were assessed in a population-based sample of 10,508 Australians.RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 14 publications
7
69
0
1
Order By: Relevance
“…So, the selector set includes: the T2DM, CVD and HT statuses, fasting glucose, age, waist-circumference-to-height ratio (WCHR), SBP lying, diabetic phenotype, joint cardio-vascular and joint cardio-neuropathic facts, graded heart function on results of ECG, combined causes of high BP, and gender. Indeed, the Australian T2DM screening protocol identifies following risk factors: [4] • People aged 55+ years;…”
Section: Novel Data Analyticsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the selector set includes: the T2DM, CVD and HT statuses, fasting glucose, age, waist-circumference-to-height ratio (WCHR), SBP lying, diabetic phenotype, joint cardio-vascular and joint cardio-neuropathic facts, graded heart function on results of ECG, combined causes of high BP, and gender. Indeed, the Australian T2DM screening protocol identifies following risk factors: [4] • People aged 55+ years;…”
Section: Novel Data Analyticsmentioning
confidence: 99%
“…[3] An Australian study has evaluated an existing in the country protocol for identification of undiagnosed T2DM and recommended the HbA1c assay as a cost effective measure to reduce amount of FPG and TPG testing. [4] HbA1c has several advantages to FPG and TPG if the erythrocyte function is normal. [5][6][7] HbA1c is a long-term indicator for plasma glucose (PG) levels as it reflects average glycaemia over the preceding 8-12 weeks [8] and is therefore considered a good surrogate marker for T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…First, screening targeted at pre-diabetes will also identify some undiagnosed cases of diabetes. The AusDiab Study in Australia found that up to half of all people with diabetes were undiagnosed, whereas in the USA the National Health and Nutrition Examination Survey in 2005/06 reported that 40% of diabetes was [13,31]. Increased case finding would increase diabetes treatment costs, but would also lead to health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines were applied to the population in the AusDiab study and the rate of identification of people with pre-diabetes was calculated [13]. Inclusion criteria of the opportunistic screening programme included: (1) age >55 years; or (2) age >45 plus high BMI, family history of type 2 diabetes or hypertension; or (3) people from 'high-risk' groups (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Case Detection and Diagnosis, June 2009 Applying the NHMRC 2002 Case Detection and Diagnosis Guideline to the AusDiab population identifies a significant proportion of the population with either IGT or IFG (Colagiuri et al, 2004). It is now well established that progression to diabetes in these people can be prevented or delayed through lifestyle modification or with a number of pharmacological agents Ramachandran et al, 2006;Knowler et al, 2005;Kosaka et al, 2005;Torgerson et al, 2004;Buchanan et al, 2002;Chiasson et al, 2002;Knowler et al, 2002;Tuomilehto et al, 2001;Pan et al, 1997).…”
Section: Outcomes (Evidence Level Ii)mentioning
confidence: 99%